Esophageal Acalasia: Pathophysiology, Diagnosis and Management - Nabila Indah Shofiyanti; M. Diaz Nursyamsu; Rifki Ahmad Eka Putra; Rieke Delya Rizkina; Shalsa Damai Akelba (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Achalasia is a rare disease, but it can lead to loss of the lower esophageal sphincter (LES) causing many complications in the gastrointestinal tract. Achalasia has a good prognosis if treated promptly, but the symptoms are non-specific. The aim of this study was to find out more about the pathophysiology, diagnosis and management of esophageal achalasia. This study was conducted on databases, such as PubMed, Google Schoolar, and Sience Direct. Inclusion criteria were free full text published in 2017-2022. The results of the literature review obtained by achalasia can cause functional obstruction at the gastroesophageal junction. Gradual neurodegeneration due to lack of non-cholinergic inhibitory ganglion cells results in an imbalance of inhibitory and excitatory neurotransmission, resulting in over-contraction of the lower esophageal sphincter and loss of regulation leading to achalasia. Although the incidence of achalasia is very rare, if not treated promptly, it will lead to airway obstruction and cause sudden death. Therapy in patients with achalasia requires long-term follow-up, as the nature of available therapy is palliative, meaning recurrence will often occur. In conclusion, achalasia is an esophageal motility disorder that causes disruption of esophageal peristalsis and malfunction of the esophageal sphincter characterized by difficulty swallowing. Although the incidence of achalasia is very rare, if not treated immediately, it will lead to respiratory obstruction and death.